PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT.AEROBUS TRANSPORT DI KOTA PEKANBARU PROVINSI RIAU - Tambunan, Jordan Matthew; Martina, Elti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the influence of service quality on customer satisfaction at PT. Aerobus Transport, located in Pekanbaru City. The background of this research stems from the crucial role that service quality plays in sustaining business operations, particularly in the intercity and interprovincial bus transportation (AKAP) sector. The research employs a quantitative approach using a survey method. A total of 100 respondents were selected through accidental sampling. The primary data collection instrument was a questionnaire, which was developed based on the five dimensions of the SERVQUAL model: tangibles, reliability, responsiveness, assurance, and empathy. The data collected were analyzed using simple linear regression, accompanied by validity and reliability tests to ensure the quality of the research instrument. The findings indicate that service quality has a significant effect on customer satisfaction. The coefficient of determination (R²) value of 0.429 suggests that 42.9% of the variation in customer satisfaction can be explained by service quality, while the remaining percentage is influenced by other factors. Among the five dimensions, reliable information and the courtesy of staff were identified as the most influential factors affecting customer satisfaction. Based on these results, it is recommended that PT. Aerobus Transport continue to improve its service quality, especially in terms of travel safety and complaint handling, to enhance customer satisfaction and foster long-term loyalty Keywords: Service Quality, Customer Satisfaction, Transportation, PT. Aerobus Transport, Pekanbaru.